2019
DOI: 10.3390/en12102022
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Measurements of Methane-Coal Adsorption and Desorption Isotherms—Effects of Equations of State and Implication for Initial Gas Reserves

Abstract: This study presents the effects of equations of state (EOSs) on methane adsorption capacity, sorption hysteresis and initial gas reserves of a medium volatile bituminous coal. The sorption experiments were performed, at temperatures of 25 °C and 40 °C and up to 7MPa pressure, using a high-pressure volumetric analyzer (HPVA-II). The measured isotherms were parameterized with the modified (three-parameter) Langmuir model. Gas compressibility factors were calculated using six popular equations of state and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 33 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…In the case of a Type III isotherm, there is no Point B (the PT data in Figure 5C) and consequently no detectable monolayer formation and the adsorbed molecules are clustered around the most favourable sites on the surface of a macro-porous solid [55]. The hysteresis loop on the N 2 gas sorption-desorption isotherm occurred in the range of 0.5 to 1.0 P/P 0 which is greater for the polymer-treated sample, implying the presence of more mesopores [56,57].…”
Section: Discussionmentioning
confidence: 96%
“…In the case of a Type III isotherm, there is no Point B (the PT data in Figure 5C) and consequently no detectable monolayer formation and the adsorbed molecules are clustered around the most favourable sites on the surface of a macro-porous solid [55]. The hysteresis loop on the N 2 gas sorption-desorption isotherm occurred in the range of 0.5 to 1.0 P/P 0 which is greater for the polymer-treated sample, implying the presence of more mesopores [56,57].…”
Section: Discussionmentioning
confidence: 96%
“…It is equipped with a Microsoft Excel ® -based software that automatically computes the isotherms using fluid data obtained from refprop ® software. Details of the formulae used in calculating the isotherms and the dependence of the isotherms on equation of state have been discussed in our previous studies [18,24]. Thus, based on the findings from those studies, the equation of state by Soave-Benedict-Webb-Rubin (SBWR-EOS) [25] was adopted to calculate the gas compressibility factors for both helium (for free-space volume calculation) and methane in this study.…”
Section: Measurements and Modeling Of Methane Adsorption And Desorptimentioning
confidence: 99%
“…Moreover, significant hysteresis can be seen between the adsorption and desorption isotherms for each sample. It is believed that the primary reason for the observed large hysteresis between the sorption isotherms for each sample is the equation of state used in calculating volume changes during the sorption processes [18]. It has been reported that both the size and type of hysteresis between methane adsorption and desorption isotherms are dependent on the applied equation of state [18].…”
Section: Contains a List Of The Key Reservoir And Wellmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the volumetric method depends on the gas equation of state, and the shrinkage effect of the coal matrix leads to an increase in free space. Meanwhile, the change in gas compressibility factor makes the calculation and correction more complicated. , In recent years, low-field nuclear magnetic resonance (LF-NMR) technology has been extensively used in reservoir fluid analysis, adsorption characteristics, and stress sensitivity. The dynamic changes of the coal reservoir during gas exploitation can be quantitatively characterized by the hydrogen-bearing fluid (e.g., CH 4 and H 2 O) relaxation time. …”
Section: Introductionmentioning
confidence: 99%